Islamic Education And Learning Technology (Lembaga Pengembangan Kinerja Dosen, 2023)
Technology advancements are inevitable in this day and age, and they have an impact on Islamic education as well. The education industry must keep up-to-date media and instructional strategies in line with information technology advancements in order to effectively implement learning technologies. Given that the current generation's learning preferences differ from those of past generations, it is critical to monitor the advancement of learning technologies. The purpose of this study is to comprehend the definition, advantages, and effects of learning technology on Islamic education. The process of gathering data involves reading and investigating books, journals, and other informational materials about learning technology, particularly as it relates to Islamic education. According to the data gathered, learning technology in Islamic education is a set of activities that are done in order to facilitate effective and efficient Islamic education learning. These activities include design, development, utilization, management, and assessment.